Surface effects on exciton diffusion in non polar ZnO/ZnMgO heterostructures. (10th November 2017) - Sakr, G; Sartel, C; Sallet, V; Lusson, A; Patriarche, G; Galtier, P; Barjon, J
Abstract: The diffusion of excitons injected in ZnO/Zn0.92 Mg0.08 O quantum well heterostructures grown by metal-organic-vapor-phase-epitaxy on non-polar ZnO substrates is investigated at room temperature. Cathodoluminescence linescans in a field-emission-gun scanning-electron-microscope are performed across cleaved cross-sections. A 55 nm diffusion length is assessed for excitons in bulk ZnMgO. When prepared as small angle bevels using focused ion beam (FIB), the effective diffusion length of excitons is shown to decrease down to 8 nm in the thinner part of the slab. This effect is attributed to non-radiative surface recombinations, with a 7  ×  10 4 cm s −1 recombination velocity estimated at the FIB-machined ZnMgO surface. The strong reduction of the diffusion extent in such thin lamellae usually used for transmission electron microscopy could be use improve the spatial resolution of cathodoluminescence images, often limited by diffusion processes.